GENERAL CHARACTERISATION OF THE CONTENT STRUCTURE OF ISLAMIC IDENTITY IN TURKISH ISLAMIC FICTION (Journal of Oriental Studies, 2024)
Islamic novels provide a unique key to comprehend the role, significance, historical profile, and evolution of Islamic identity within Turkey's political system. These literary works also provide an opportunity to grasp the Islamic movement's struggle for dominance, political rhetoric, and practices based on the emerging Islamic classes. The primary objective of these Islamic novels was to establish an alternative Islamic model, an Islamic society based on a collective "we," by defining and justifying the incompatibility of Islam and modernization. Consequently, it was necessary to confront “them” (“the other”) first, before turning to the source of self-knowledge and self-expression, the “Golden Age”. However, the definition of Islamic identity as interpreted by the “Golden Age” has changed since the 1990s, when texts were written criticizing the monolithic structure of Islamic identity, isolation from the outside world, and the androcentric structure of Islamism.
Keywords: Islam; Identity; Golden Age; Modernization; Turkish Literature; the West; Incompatibility; Conversion